MUTU BUBUK CABAI HASIL PENGERINGAN ENERGI MATAHARI DENGAN SUMBER PANAS PENGGANTI [Chilli Powder Quality Dried Using Solar Dryer With Heat Source Energy Replacement] - Tongkeles, Nelly S.; Djarkasi, Gregoria S.S.; Wenur, Frans (Jurnal Ilmu dan Teknologi Pangan, 2014)
Solar dryer with heat source energy replacement is one of environmental drying technology. This research aimed to determine water content, color analysis, vitamin C, total molds from chili powder, and dried chilli yield as quality for dried chili. Results showed moisture content of dried Red chilli and Local Chilli using solar dryer with heat source energy replacement are 7.3%bb and 6.24%bb, needs 10 hours and 8 hours respectively. Whereas moisture content of the same materials with conventional drying method are 11.89%bb and 8.63%bb, needs 71 hours and 41 hours respectively. Furthermore, color analysis of dried Red chili and Local Chilli and its powder using a dryer gives value of â€‹L a+ b+ higher than same materials and its powder with conventional drying methods. Vitamin C content on powder of those materials using a drier is higher at 54.33mg/100g and 27.73mg/100g respectively, while with the same material by conventional drying methods implies that 36.33 mg/100g and 8.60 mg/100g. Total mold analysis has highest value on Red chilli powder and Local Chilli powder with conventional drying methods are 6.46x102 colonies/g and 2.06x102 colonies/g. Whereas Local Chilli powder which dried using a dryer there is no mold, followed by dried Red chilli powder that is 1.1x102 colonies / g. The yield of dried Red chillies and Local Chilli ranged between 24.97%-32.17%, whereas the yield of dried chili with conventional methods is lower than using a dryer. Â  Key word: Quality, Chilli powder, Solar dryer